MODEL APLIKASI KOMUNIKASI DARING SEBAGAI FASILITAS PEMBELAJARAN DI ERA PANDEMI COVID 19 - Ahmad Fahrudin (Indonesian Journal of Islamic Communication, 2021)
Abstrac: Education is one of the most important things in human life, the purpose of education is a change towards good quality. This is one indication that education runs dynamically. The existence of a pandemic has also forced the role of education policy makers to create a new strategy in the teaching and learning process, one of which is given a solution to learn in a bold way. So there are several applications that can be used for communication in bold learning. This study uses an approach in this study using a qualitative descriptive approach using a more detailed approach, namely phenomenology. The results obtained from this study are that communication application users are indeed very strong, especially in the Aplikasi Rumah Belajar (ARB) accessible Sumber Belajar they get the following data: 2,767,9012, Kelas Digital 5,409,919, Laboratotium Maya 297,020, and for Bank Soal as many as 8,765,200.